FACTORS AND METHODOLOGICAL APPROACHES INFLUENCING THE INNOVATION MANAGEMENT MECHANISM IN THE HIGHER EDUCATION SYSTEM (Marketing Journal, 2025)
This article analyzes the factors and methodological approaches influencing the mechanism of innovation management in the higher education system. Also, the American economist and sociologist C. Rogers developed a classification of groups for the developme nt and implementation of innovations by professors and teachers in educational institutions, as well as a methodology for innovation management in the higher education system.
Keywords: Comprehensive study plan; innovative study plan; innovative dual education; innovative university; financial independence; Cash back Agreement